Assentamentos rurais : uma análise da competitividade : o caso do município de Campo Verde - Härter, André Covari (2016)
The Brazil and its history are marked by polarized politics, in which favor the employer agriculture at the expense of family farming, not being different in Mato Grosso and Campo Verde. Simple access to land is no guarantee of income and success of settlement projects. The strongest way to develop is to enter the settlements competitively in the market. To this end, the question is: what are the factors that influence the competitiveness (in the ex-ante view) of rural settlements of Campo Verde? In this perspective, it is suggested after diagnosis using SWOT analysis, different strategies for each settlement, aiming to propose development guidelines. stand out among many points in common, very favorable geographical features to do many productive ways, size of appropriate property, location close to markets and portfolio of products suitable as strengths; poor education, lack of expertise, lack of hand work, as weaknesses; favorable climate to develop numerous productive ways, there are many fairs and markets in the vicinity, constant interaction with buyers and sellers circulating in the region, access to education by the younger generations and favorable credit lines available as opportunities; and the absence of regular official and technical assistance, lack of land titling, hand competition work with agribusiness, agrarian and environmental legislation, weakness in associative organizations and dependence with buyers and middlemen as threats.